Fluid consumption, exercise, and cognitive performance - Backes, TP; Fitzgerald, K (Biology of Sport, 2016)
Laboratory evidence supports the notion that dehydration degrades exercise performance and impairs certain cognitive processes. The purpose of this study is to examine the effect of a voluntary versus a dictated drinking condition on exercise and cognitive performance. The study used a double-blind and paired design. Twenty male and female college students (10 women, 10 men) participated in an exercise protocol consisting of 1 hr of treadmill running followed by a high intensity portion continuing until voluntary exhaustion. The dictated drinking condition consisted of 900 ml of water equally distributed in 4 pre-prepared opaque bottles. At 15 min intervals the subject was instructed to drink the entire contents until the end of the 1 hr treadmill protocol. The voluntary drinking condition consisted of 225 ml of water within arm’s reach of the subjects while on the treadmill. Exercise performance was significantly better (longer duration and faster speed) in the voluntary condition compared with the dictated condition. Cognitive test outcomes were not significantly different between drinking conditions. A difference in fluid absorption is a potential source of exercise impairment seen in the dictated fluid condition. The higher fluid consumption rate presumably would cause greater gastric and esophageal distention resulting in the diversion of blood flow from working muscles to the gastrointestinal system. In situations where dehydration is likely, drinking to recommended guidelines may protect individuals from dehydration and its negative effects. However, when dehydration is not likely, allowing an individual to follow voluntary drinking behavior is preferable for exercise performance.